(untitled) (Revista Apotheke, 2024)
This article seeks to weave relations between art and science to insubordinate other insurgent practices relationship between art and science. We are challenged to think about other modes of knowledge production through the concept “the modes of existence” coined by the philosopher Etienne Souriau. Challenged to give other existences (visibilities) to the relationships between birds and planes, children create a hybrid nature through drawings and prototypes. Thus, they break the dichotomy and dualism so present in the concepts of culture and nature and invent another way of understanding the world in which they are inserted, making the act of learning an investigative, fun, and creative exercise.